PEMANFAATAN HASIL NITRIFIKASI LIMBAH CAIR PERIKANAN SECARA BIOLOGIS SEBAGAI PUPUK NITROGEN PADA TANAMAN BAYAM (Amaranthus sp.) - BUSTAMI IBRAHIM; ANNA C. ERUNGAN; IRMA IRMA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2010)
Indonesian’s fish processing industry developed very rapidly. During the operational production, these industries consumed clean water in enorrmous volume, as much as wastewater has been produced. One of technologies frequently used is using wasterwater aeration pond. This clean treated wastewater can be used as a liquid organic fertilizer, as it contains nutrient such as N, P and K which is good for growing plant. The research objective is to study utilization of treated fishery industry wastewater by activated sludge as a liquid organic fertilizer for growing of spinach vegetable (Amaranthus sp.). The study resulted that spinach fertilized by liquid treated wastewater grew better than the one that fertilized by other treatments. Concentration of liquid fertilizer from wastewater within treatment was not significant.